Bait off-color stories for you to color - Palahniuk, Chuck 1962- (Dark Horse Books, 2016)
"Bestselling novelist Chuck Palahniuk presents Bait: Off-Color Stories for You to Color, his first ever coloring book for adults. Bait is both the coloring book debut and the second short story collection for Palahniuk, author of Lullaby and Fight Club. The 8.5 x 11 inch hardcover album contains eight tales, illustrated in detailed black and white"...Provided by publisher